Perspectives on antimicrobial use in pig and layer farms in thailand: legislation, policy, regulations and potential - Aniroot Nuangmek; Suvichai Rojanasthien; Panuwat Yamsakul; Pakpoom Tadee; Thanaporn Eiamsam-ang; Visanu Thamlikitkul; Nattasit Tansakul; Manat Suwan; Teerarat Prasertsee; Suwit Chotinun; Prapas Patchanee (Veterinary Integrative Sciences, 2020)
Irrational use of antimicrobials is a major problem worldwide. The comprehensiveness of the existing legislation and veterinary pharmaceutical regulatory system has been critically evaluated and its practical implementation was assessed in this study. A cross-sectional survey study, and an in-depth interview of key informants involving the layer and pig farm owners/managers of farms located in Chiang Mai, Lamphun and Chonburi Provinces were conducted. The Thai FDA is responsible for pre-marketing and authorizes relevant officials of DLD to enforce drug acts related to the post-marketing of veterinary drugs/biologics. These existing legislations and regulations were comprehensive enough to cover all areas of pharmaceutical activities developed to protect the health of the public and animals in the country; however, the enforcement of these rules may not be properly enforced or may be ineffectively executed. Rules regarding veterinary pharmaceuticals being distributed throughout the country have not been clearly stated. Farmers can easily access veterinary pharmaceuticals, and veterinarian prescriptions were not needed. Additionally, the relevant benefits were among the most important reasons for choosing to use antimicrobials on farms, along with a lack of availability of better alternative products for the treatment of infections. Intensive legislation and regulation enforcement were considered to be the most effective means of reducing antimicrobial usage and abuse in Thailand.